Factors associated with stress among pregnant women with a second child in Hunan province under China’s two-child policy: a mixed-method study - Zhang, Lijuan; Huang, Ruirui; Lei, Jun; Liu, Yongrong; Liu, Dan (BMC psychiatry, 2024)
Objective The purpose of the study was to investigate the status of pregnancy stress and to explore factors associated with pregnancy stress among women by China’s two-child policy. Methods A mixed-method study involving both quantitative and qualitative methods was conducted using questionnaires and semi-structured interviews. The questionnaires encompassed socio-demographic and obstetric characteristics, as well as the Pregnancy Stress Rating Scale (PSRS) and the Social Support Rating Scale (SSRS). Initially, the participants were required to complete the questionnaires, enabling us to assess their respective pregnancy stress statuses. Subsequently, we selectively interviewed pregnant women with a second child and exhibited at least mild pregnancy stress. The qualitative study sought to uncover the factors contributing to their stress during pregnancy. Results A total of 463 subjects were enrolled; of the subjects, 22 (4.8%) had no stress, 407 (87.9%) had mild stress, 34 (7.3%) had moderate stress. Generalized linear regression analysis revealed significant factors ( P <0.05) related to pregnancy stress, including family financial burden, subjective support, fertility desire, gender of the first child, and gender preference. Additionally, 16 subjects were interviewed, and through analysis, three major themes emerged, each comprising 12 sub-themes associated with pregnancy stress. These themes were identified as fertility factors (worry about maternal and child health, birth experience, and parenting stress), family factors ( financial burden, second child care problems, first child’s acceptance of the second child, family concerns, fertility desire, and gender preference) and social factors (involving life events, career development and workload). Conclusion The diver factors contribute to pregnancy stress among pregnant women under China’s two-child policy. Our study could be used to develop appropriate interventions to reduce pregnancy stress and to enhance the mental health of women pregnant with a second child.